A spatial analysis of intensity in tourism accommodation: An application for Extremadura (Spain) - María Cristina Rodríguez Rangel; Marcelino Sánchez Rivero; Julián Ramajo Hernández (Economies, 2020)
There is a general belief that the distribution of tourist activity in space does not respond to a random pattern, so having a thorough knowledge of said activity will require analyzing and understanding its distribution pattern. At the same time, the adequate planning of this sector requires exhaustive knowledge, on the one hand to be able to enhance the positive effects of concentrations in the space, and on the other hand to avoid those possible adverse effects. Therefore, various studies focus on providing information on the random pattern of these activities, especially in developing destinations with a great interest in generating a model of sustainable tourism development. This paper aims to contrast the results achieved by previous studies at the destination while describing the pattern identified through the use of alternative statistical techniques rather than those commonly used. In particular, an intensity function is estimated using three different methods: quadrant counting, K-function, and kernel smoothing. The results achieved allow the identification of the areas with the greatest tourist intensity while describing the practical implications of the results achieved.
Keywords: 330; accommodation; Extremadura; kernel density; quadrant counting; Ripley's function; spatial homogeneity; spatial point patter (SPP); tourist planning